(untitled) (Global Journal of Management and Business Research, 2014)
Customers are more particular about shelf life, taste and nutritious value of products when it comes to perishables, as compared to non-perishables, especially food items. Decisions related to stock size, price discounts, and aftershelf-life uses of such goods are relatively difficult to take. The majority of wholesaler of perishables generally manages their inventories and profit on know-how basis rather than using any objective criteria. This paper is based on a study conducted lately by the authors on inventory management and performance of supply chains of perishables. Monte Carlo simulation approach is used in this paper to find out economic stock size, amount and period of price discounts, and expected profit for wholesalers supplying eggs to a local market. The framework of this study has been adapted from two previously published studies on a related issue.